Baveno VI Recommendation on Avoidance of Screening Endoscopy in Cirrhotic Patients: Are We There Yet - Silva,Mário Jorge (2017)
Introduction: Recent studies assessed the predictive value of liver transient elastography, combined or not with platelet count, for the presence of esophageal varices in patients with liver cirrhosis, and multiple cutoffs have been proposed. The Baveno VI consensus states that patients with compensated advanced chronic liver disease, liver stiffness <20 kPa, and a platelet count >150,000 have a very low risk of having varices requiring treatment and can avoid screening endoscopy. We aimed to validate this recommendation in a cohort of cirrhotic patients. Methods: Retrospective analysis of all patients evaluated at the Gastroenterology Department (Centro Hospitalar de Lisboa Central) between September 2009 and October 2015 with a liver stiffness (FibroScan ® ) compatible with liver cirrhosis as well as upper endoscopy and blood tests within 12 months from elastography. Patients on propranolol ≥ 80 mg/day or carvedilol ≥ 12.5 mg/ day, as well as those with previous variceal bleeding, variceal endoscopic treatments, or cirrhosis decompensations were excluded. We validated the new Baveno VI recommendation and explored alternative cutoffs. Results: Ninety-seven patients were analyzed, 76.3% (74/97) male, mean age 54.3 ± 11.2 years. Most patients (55.7%) had no varices and 14.4% had varices requiring treatment. Most patients (78.4%) had cirrhosis related to chronic hepatitis C. If the new Baveno VI recommendation had been applied to this cohort, upper endoscopy would have been avoided in 11.3% (11/97) of patients, none of them with esophageal varices requiring treatment: specificity 100%, sensitivity 13.3%, positive predictive value 100%, and negative predictive value 16.3% for absence of varices requiring treatment. If screening endoscopy had been avoided in those patients with liver stiffness <30 kPa and platelet count ≥ 120,000, endoscopy would have been avoided in 27.8% (27/97) of patients, none of whom with esophageal varices requiring treatment: specificity 100%, sensitivity 32.5%, positive predictive value 100%, and negative predictive value 20% for absence of varices requiring treatment. Conclusions: The new Baveno VI criteria identified compensated cirrhotic patients without varices requiring treatment in whom screening endoscopy could havebeen avoided safely. Further studies are needed to confirm these findings and potentially explore more ambitious but still safe cutoffs for those criteria.